The effect of ezetimibe on lipid and glucose metabolism after a fat and glucose load - Hiramitsu, Shinya; Miyagishima, Kenji; Ishii, Junichi; Matsui, Shigeru; Naruse, Hiroyuki; Shiino, Kenji; Kitagawa, Fumihiko; Ozaki, Yukio (Journal of cardiology, 2012)
The clinical benefit of ezetimibe, an intestinal cholesterol transporter inhibitor, for treatment of postprandial hyperlipidemia was assessed in subjects who ingested a high-fat and high-glucose test meal to mimic westernized diet. We enrolled 20 male volunteers who had at least one of the following: waist circumference ≥ 85cm, body mass index ≥ 25kg/m2, or triglycerides (TG) from 150 to 400mg/dL. After 4 weeks of treatment with ezetimibe (10mg/day), the subjects ingested a high-fat and high-glucose meal. Then changes in serum lipid and glucose levels were monitored after 0, 2, 4, and 6h, and the area under the curve (AUC) was calculated for the change in each parameter. At 4 and 6h postprandially, TG levels were decreased (p<0.01) after 4 weeks of ezetimibe treatment, and the AUC for TG was also decreased (p<0.01). Apolipoprotein B48 (apo-B48) levels at 4 and 6h postprandially were significantly decreased after ezetimibe treatment (p<0.01 and p<0.001, respectively), and the AUC for apo-B48 was also significantly decreased (p<0.01). Blood glucose and insulin levels at 2h postprandially were significantly decreased by ezetimibe (p<0.05). The AUCs for blood glucose and insulin were also significantly decreased (p<0.05 and p<0.01, respectively). Since ezetimibe improved postprandial lipid and glucose metabolism, this drug is likely to be beneficial for dyslipidemia in patients with postprandial metabolic abnormalities.